2016
DOI: 10.4014/jmb.1511.11003
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Characterization of Recombinant UDP-Glucose:Sterol 3-O-Glycosyltransferase from Micromonospora rhodorangea ATCC 31603 and Enzymatic Biosynthesis of Sterol-3-O-��-Glucosides

Abstract: A uridine diphosphate-glucose:sterol glycosyltransferase-encoding gene was isolated and cloned from the established fosmid library of Micromonospora rhodorangea ATCC 27932 that usually produces the aminoglycoside antibiotic geneticin. The gene consists of 1,185 base pairs and encodes a 41.4 kDa protein, which was heterologously expressed in Escherichia coli BL21(DE3). In silico analyses of the deduced gene product suggested that it is a member of the family 1 glycosyltransferases. The recombinant protein MrSGT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 0 publications
2
12
0
Order By: Relevance
“…The purified His-tagged recombinant MrSGT was prepared as previously described in our recent publication (Hoang et al 2016 ). The authentic sterols such as β-sitosterol, campesterol and cholesterol (Fig.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The purified His-tagged recombinant MrSGT was prepared as previously described in our recent publication (Hoang et al 2016 ). The authentic sterols such as β-sitosterol, campesterol and cholesterol (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Qualitative analyses of the sterols and sterol glucosides (including β-sitosterol-3- O -β- d -glucoside, campesterol-3- O -β- d -glucoside and cholesterol-3- O -β- d -glucoside) obtained from the in vitro MrSGT reactions were conducted by HPLC-tandem mass spectrometry (MS/MS; ThermoFinnigan, San Jose, CA, USA) as described before (Hoang et al 2016 ). In brief, isocratic elution (methanol:acetonitrile:water:formic acid = 45:40:14.8:0.2 [v/v/v/v]) was performed on an Acquity CSH C 18 reversed-phase column (Waters, Milford, MA, USA; 2.1 × 50 mm, 1.7 μm) at a flow rate of 120 μL/min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been several biotechnological advancements using the SG metabolism enzymes, but not SGs themselves. These advancements span the food industry, agriculture, medicinal, and crystallization assays [6,72,73,80,[85][86][87]. Three important studies showed the importance and uses of SGs in these fields.…”
Section: Biotechnology and Industrial Usesmentioning
confidence: 99%
“…First, since SGs are made in such small amounts in cells, a means to mass produce will possibly be needed in the future, especially if our hypothesis regarding SGs as an immunoadjuvant holds true. One 2016 study reported the biochemical characterization of a steryl glycosyltransferase enzyme from the bacteria Micromonospora rhodorangea ATCC 31,603 [85]. This was a unique characterization since this SGT enzyme preferred phytosterols (plant sterols including sitosterol, stigmasterol, and campesterol) to cholesterol when making SGs.…”
Section: Biotechnology and Industrial Usesmentioning
confidence: 99%